(untitled) (Canadian Journal of Native Studies, 2026)
The relationship between Canadian state agencies and First Nations, Inuit, and Métis peoples has long been one of control, domination, and exploitation. Research on this relationship can contribute to decolonization by revealing how Canada exercises state colonial power, and conversely, how such power has been resisted. One tool that has been used in this type of research is Freedom of Information (FOI) and Access to Information (ATI) requests. FOI and ATI requests are used to obtain government information and records and are increasingly used in social science research. The ability for FOI researchers to make requests strengthens the credibility of their work while serving as an exercise in empowerment by accessing information otherwise guarded by institutions. We sought to answer two questions: (1) How can FOI/ATI requests be used to decolonize research, and (2) What does it mean for ethics and critical research to view FOI/ATI requests in this way, particularly for settler researchers? Both questions were answered by examining existing literature that used FOI/ATI requests in their research on Canadian state agencies that govern First Nations, Inuit, and Métis peoples.